ACE in Singapore: Floating fish farm for food security and sustainability - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 2024)
The case is set in April 2023, five years since Leow Ban Tat, CEO of Aquaculture Centre of Excellence Pte Ltd (ACE), founded the Singapore-based seafood start-up with the objective to rear healthy fish sustainably and help Singapore improve its food security and self-sufficiency. ACE’s fish farm ‘Eco-Ark’ was an innovative floating closed container system. It was based on Leow’s patented technologies – a combination of offshore, marine, and recirculating aquaculture technologies – which helped keep its fish safe from pollutants, pathogens and variations in oxygen and temperature in the sea water, besides minimising the fish farm’s carbon footprint. With a hatchery and a processing facility added on board within a year of Eco-Ark starting its operations, ACE offered a fully traceable and integrated value chain from locally sourced eggs to ready-to-use products and one of the shortest fish food production miles in aquaculture. Going forward, Leow planned to undertake egg production as well, to have full control over ACE’s supply chain. He also planned to increase ACE’s footprint by launching more Eco-Arks in Singapore and internationally, and licensing Eco-Ark’s innovative and unique technology to other farms. However, despite healthier and sustainable offerings, the market demand for ACE’s products had remained lower than hoped for, largely because of its price premium over cheaper fish imports. Although supported by the Singapore government in its endeavours, the company struggled to cover its expenses and keep afloat. Fully committed to the sustainability vision, Leow believed that his breakthrough design and process would be transformational in the future. However, he wondered how long the company would be able to sustain its operations given the sluggish sales and aggressive competition. What could be done? Students will learn about the importance of producing healthier and more sustainable seafood and understand the role of technological innovation leadership in developing operations capable of producing that. They will also get to analyse ACE’s commercial challenges and apply relevant marketing and management concepts, such as segmentation, competitive forces, generic strategic options, and value proposition (Business Model Canvas) - to improve the firm’s operational model and profitability.